2018
DOI: 10.1016/j.rmed.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of infliximab biosimilar Inflectra® in severe sarcoidosis

Abstract: Infliximab biosimilar Inflectra seems effective in the treatment of refractory sarcoidosis with a comparable safety profile to the reference product Remicade. Inflectra can be considered as an alternative and less expensive option for patients with refractory sarcoidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 33 publications
1
21
0
1
Order By: Relevance
“…Adalimumab has also been used, although to a lesser extent [13,14]. Nowadays, biosimilars are commonly used and have proved to be effective and safe as well [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Adalimumab has also been used, although to a lesser extent [13,14]. Nowadays, biosimilars are commonly used and have proved to be effective and safe as well [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…After 26 weeks of infliximab treatment, mean improvement in FVC was 6.6% predicted (p = 0.0007), whereas in the 6 months before treatment, lung function decreased. Maximum standardized uptake values (SUVmax) of the pulmonary parenchyma at baseline correlated significantly with FVC improvement during treatment (R = 0.62, p = 0.0004), which was confirmed in patients treated with an infliximab biosimilar [64].…”
Section: Pulmonary Function Tests and Fdg-positive Lung Parenchymal Dmentioning
confidence: 72%
“…92 Schimmelpennink et al recently reported in a retrospective study of 29 patients that the IFX biosimilar (i.e., Inflectra ® ) appears to be effective in the treatment of refractory sarcoidosis with a profile comparable to the reference. 93 In contrast to randomized controlled trials versus placebo, in retrospective and open-labeled studies TNFi had more overall and serious adverse events and more severe infections. These adverse events seemed to be more frequent during sarcoidosis treatment than during other inflammatory diseases.…”
Section: Tnf-α Inhibitorsmentioning
confidence: 99%